Human organ trade: trending issues and the relationship to access to justice (2017)
In a world facing a constant battle between the law and crime, yet another offspring of crime is unabashedly conceived and manages to seep out despite all attempts by the justice systems all over the world to eliminate or mitigate to the barest minimum crime in all its forms. Human organ trade is a new trend in crime and is in fact fast topping the echelons of criminal strata and is indeed a very deadly crime to battle with the question one might ask is, how long is the hand of the law or better put, how efficient is the machinery of the law in curbing this fast rising global trend in crime before it becomes a subject of historical wreckage? This paper wishes to discuss the meaning and definition of human organ trade, the historical background, global trends, prevalence in Nigeria, legal provisions of organ trade, the effects of organ trade globally and recommendations on how this new trend in crime can be weeded out before it grows to become too much of a thorn in the flesh globally.